2021
DOI: 10.1016/j.ygeno.2020.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Variant analysis of the first Lebanese SARS-CoV-2 isolates

Abstract: Recently the first genome sequences for 11 SARS-CoV-2 isolates from Lebanon became available. Here, we report the detection of variants within the genome of these strains. Pairwise alignment analysis using blastx was performed between these sequences and the UniProtKB data for the SARS-CoV-2 coronavirus to identify amino acid variations. Variants analysis was performed using multiple Bioinformatics tools. We noticed for the first time 18 mutations that have never been reported before. Among those, a frame shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The results of a study that investigated only eleven full-length genome sequences from Lebanon until Mar 2020, showed that the most prevalent variants were 23403A > G (D614G), clade G, and the second common mutant was 14408C > T, in ORF1ab, resulted in a missense mutation as P4715L, one of the three mutations mostly co-occurred with 23403A > G harboring genome. The pattern of variations in this study was equal to the European countries, at the same time which is rational according to their short distances [92] .…”
Section: Geographic Distribution Of Sars-cov-2 Mutationssupporting
confidence: 64%
“…The results of a study that investigated only eleven full-length genome sequences from Lebanon until Mar 2020, showed that the most prevalent variants were 23403A > G (D614G), clade G, and the second common mutant was 14408C > T, in ORF1ab, resulted in a missense mutation as P4715L, one of the three mutations mostly co-occurred with 23403A > G harboring genome. The pattern of variations in this study was equal to the European countries, at the same time which is rational according to their short distances [92] .…”
Section: Geographic Distribution Of Sars-cov-2 Mutationssupporting
confidence: 64%
“…The genomes of 11 Lebanese strains were previously analyzed and showed a number of mutations in the ORF of structural and nonstructural proteins [26,27]. A total of 40 single nucleotide variations were detected in the analyzed strains and resulted in amino acid changes, a stop codon, a frameshift, and a deletion.…”
Section: Introductionmentioning
confidence: 99%
“…With accumulating genome wide errors 495 in coding and non-coding sequences of emerging 496 variants, the impact of errors on SARS-CoV-2 proteins may influence the mortality and morbidity due to SARS-CoV-2 infection. Spike protein RBD is an element in this set and may remain as the prominent antigen of choice for mRNA vaccines, albeit in the short-term.…”
Section: Appendix IV -Aptamers As Adjuvants And/or Parallel Alternatimentioning
confidence: 99%